Training on Aglaonema Ornamental Plant Cultivation to Improve Self-Employment Ability of Learners of Community Learning Community (CLC) in Malang Regency - Rezka Arina Rahma; Zulkarnain Zulkarnain; Sri Wahyuni; Ellyn Sugeng Desyanty (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Community Learning Center (CLC/PKBM) is one of the non-formal education units that provides a place for learning for the community with learning that formal education does not have. Establishing CLC is to organize learning that can improve the community's welfare through independent business competencies. Communities as learners have expectations of the learning obtained by providing them with previous experiences. However, not all CLCs can provide this experience. This results in problems for learners who are not motivated, cannot capture the information provided, and cannot take advantage of scientific opportunities to solve problems in their lives. Therefore, adaptive, innovative, and creative learning is needed to meet the needs of learners in order to be empowered. The cultivation of this type of aglaonema ornamental plant was chosen because this plant experienced an increase in fame during Covid-19. This is also because it is easy to care for, can be cultivated at home, and can clean dirty air. Based on these reasons, this aglaonema plant has the opportunity to become one of the entrepreneurs by learning from residents. The method used is andragogy in the form of training. In addition to training methods, resource persons' mentoring is also applied to learners. The results of this activity are increasing knowledge of aglaonema ornamental plant cultivation for CLC learners, increasing independent entrepreneurship skills for learners, fostering an attitude of responsibility, and having a high work ethic in facing challenges.